Secondary acute myeloblastic leukemia after adjuvant chemotherapy and radiotherapy in breast cancer: A case report - Hardianti, Mardiah Suci; Kurnianda, Johan; Taroeno-Hariadi, Kartika Widayati (Universitas Gadjah Mada, 2014)
A rising number of long-term survivors and potential long-term outcome related to the treatment isone of the most important issue due to the advances of management in cancer. The development ofsecondary malignancy has been reported in a number of cohorts. We present a case of breast cancerpatient developing acute myeloid leukemia (AML)- M5 within a relatively short interval of two and ahalf years from her primary treatment with adjuvant chemotherapy with 4 cycles of doxorubicin andcyclophosphamide, followed by 4 cycles of three weekly paclitaxel (AC-T) and radiotherapy. Whatcould be attributed to the occurrence of secondary leukemia in this patient will be discussed.